Unpredictable effects of short term marihuana (cannabis) use in a male: gynecomastia and oligoasthenospermia - Bayraktaroğlu, Taner; Kargı, Eksal; Yeşilli, Çetin; Numanoğlu, Gamze; Borazan, Ali; Üstündağ, Yücel (Journal of Dependence, 2004)
We aimed to present a case with oligoasthenospermia and gynecomastia after short term use of marihuana (cannabis).Case: Thirty one years-old male admitted with complaint of sensation of mass in his left breast for the last 20 days. He was using cannabis for 15 days before noticing the mass. At physical examination; he had a subareolar non-tender mass in his left breast which was approximately 50 millimeters in diameter and without signs of fixation into surrounding tissue. The patient had elevated serum estradiole levels. Sperm analysis revealed decreased sperm count and loss of sperm motility. Breast sonography revealed a hypoechoic mass 45x35x25 millimeters in diameters in his left breast. Abdominal and scrotal sonographic examinations were normal. Total excision of the defined mass revealed hypertrophic mammary glands with cystic dilatations of several ductal structure in a fibroadipose tissue. There was no sign of atypia and or dysplasia. Gynecomastia was diagnosed and no further treatment was planned. He was called for routine follow up. During the next one year, he did not use cannabis and gynecomastia did not reappear. His control serum estradiol levels were decreased to normal ranges. Moreover; control sperm analyses were also evaluated as nearly normal. This case suggests that even short term use of cannabis can lead to gynecomastia and oligoasthenospermia.
Keywords: Marihuana; cannabis; gynecomastia; oli-goasthenospermia